The Role of Organizational Citizenship Behavior in Mediating Organizational Support and Employee Engagement on Organizational Performance - Sukma Pratama; Ahmad Mukhlis; Angrian Permana (Yayasan Vifada Cendikia Indonesia, 2026)
Purpose: This study examines the pathways linking organizational support and Employee Engagement to organizational performance. Research Method: The study employed a quantitative design, with data collected during a single observation period. All 87 employees included in the research population were involved through a saturated sampling technique. Results and Discussion: The model estimation results demonstrate that organizational support and Employee Engagement both exert positive and significant effects on organizational performance. These two factors also encourage the development of Organizational Citizenship Behavior. In the subsequent pathway, such voluntary behavior was shown to contribute to strengthening organizational achievement. Implications: These findings indicate that improving the performance of regional government agencies cannot rely solely on formal regulations and divisions of responsibility, but also requires supportive work experiences, employees’ psychological engagement, and a willingness to make additional contributions to the organization. Originality: This research integrates organizational support, Employee Engagement, and OCB in one research model directed at the performance of local government organizations